2011
DOI: 10.12968/bjon.2011.20.12.743
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality in nursing: a systematic review of the literature from 2006–10

Abstract: Definitions of spiritual care vary, and the concept of spirituality in nursing is still under development. However, until a common language of spirituality is developed, models of spiritual care developed through research involving mainly nursing staff will be difficult for nurses to apply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 51 publications
2
87
0
14
Order By: Relevance
“…Nurses are required to carry out comprehensive assessments taking into account the patient's spirituality (WHO, 2002, NMC, 2010, but this activity may be challenging because of the ambiguous nature of spirituality (Narayanasamy, 2004, Pike, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are required to carry out comprehensive assessments taking into account the patient's spirituality (WHO, 2002, NMC, 2010, but this activity may be challenging because of the ambiguous nature of spirituality (Narayanasamy, 2004, Pike, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…This has been particularly evident in Western Society in terms of a shift away from institutionalized religion and movement towards more individualised type religion e.g., a personal search for meaning, a sense of self and enhanced connection with others ). This has led to an increased focus on spirituality and spiritual concepts across many fields including healthcare (Cockell and McSherry 2012;Monod et al 2011;Pike 2011;Williams and Sternthal 2007) and business or workplace literature (Crossman 2010(Crossman , 2011Karakas 2010;Pawar 2009;Phipps 2012). Spirituality has almost become regarded as a new concept, with a lack of recognition amongst some authors of the historical and traditional association between spirituality, religion and health.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple studies have revealed how nurses feel less competent in addressing spiritual care issues (Pike, 2011). In an attempt to bridge that incompetency, Meyer (2003) emphasized the need for nursing programs to expand education on spirituality which will help students gain more awareness of their own spirituality and allow them to administer quality spiritual care to patients.…”
Section: Spiritual Care Educationmentioning
confidence: 99%